VD_FINDINFO HC / 2013 / 781 vom 18. November 2013 - VD Tribunal cantonal (2013)
ÉCOULEMENT DES EAUX, CONDUITETUYAU | 679 CC, 689 CC, 690 CC, 308 al. 1 let. a CPC (CH), 310 CPC (CH), 404 al. 1 CPC (CH), 405 al. 1 CPC (CH)